Amazonian Medicine and the Psychedelic Revival: Considering the “Dieta” - O’Shaughnessy, David M.; Berlowitz, Ilana (Frontiers in Pharmacology, 2021)
Background. In Peruvian Amazonian medicine, plant diets (dietas) are a fundamental and highly flexible technique with a variety of uses: from treating and preventing illness, to increasing strength and resilience, to rites of passage, and even learning medicine itself. Many of the plants used in diets are psychoactive; for example, one now well known plant that can be dieted is Banisteriopsis caapi—the vine also used in the psychoactive brew ayahuasca. The use of ayahuasca has attracted increasing clinical attention towards Amazonian medicine in recent decades, and much work has focused on the potent DMT-containing ayahuasca brew, thus placing the tradition within the purview of psychedelic science. Aims. In comparison to ayahuasca, the properties of diets have been less studied, and we draw on data on the Amazonian diet as a medical practice. The investigation thus aimed to expand the conceptual field of Amazonian medicine, particularly in the context of a renewed psychedelic science and its theoretical concepts. Design. We used qualitative data from semi-structured interviews with Amazonian healers, applying a thematic analysis and contrasting findings with the available literature. Setting. Interviews were conducted in various locations in the San Martín province of Peru between 2015–2017. Participants. We selected and interviewed eight healers who had been extensively trained in traditional Amazonian medicine. Measures. Semi-structured interviews were used to gain insight into the healers’ personal experiences with plant diets. Conclusions. Diets are complex but understudied medical systems that should not be explained by reference to pharmacology or psychology only. Intercultural and interdisciplinary research programmes are called for in order to not only better understand plant diets, but traditional Amazonian medicine on the whole.